Inventing the electronic century : the epic story of the consumer electronics and computer industries : with a new preface - Chandler, Alfred D. (Alfred Dupont), 1918-2007 (Harvard studies in business history ;, 2005)
Consumer electronics and computers redefined life and work in the twentieth century. In Inventing the Electronic Century, Pulitzer Prize-winning business historian Alfred D. Chandler, Jr. traces their origins and worldwide development. From electronics prime mover RCA in the 1920s to Sony and Matsushita's dramatic rise in the 1970s; from IBM's dominance in computer technology in the 1950s to Microsoft's stunning example of the creation of competitive advantage, this masterful analysis is essential reading for every manager and student of technology.